Proceedings of the 51st Annual ACM SIGACT Symposium on Theory of Computing 2019
DOI: 10.1145/3313276.3316405
|View full text |Cite
|
Sign up to set email alerts
|

Optimal (and benchmark-optimal) competition complexity for additive buyers over independent items

Abstract: The Competition Complexity of an auction setting refers to the number of additional bidders necessary in order for the (deterministic, prior-independent, dominant strategy truthful) Vickrey-Clarke-Groves mechanism to achieve greater revenue than the (randomized, priordependent, Bayesian-truthful) optimal mechanism without the additional bidders.We prove that the competition complexity of n bidders with additive valuations over m independent items is at most n(ln(1 + m/n) + 2), and also at most 9 √ nm. When n ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The work by Eden et al [2017] found the first such result that beats the optimal revenue for the additive setting, while Feldman et al [2018] improve the bounds on the number of added buyers drastically, but they only recover a (1 − ε)-fraction of the optimal revenue. Very recent work of Beyhaghi and Weinberg [2018] match these bounds in the small market regime and drastically improve the bounds of Eden et al [2017] in the large market regime, even though the [Beyhaghi and Weinberg, 2018] results are for precise coverage of the optimal revenue. While all the above papers presents BK-style results for revenue maximization in one-sided markets, our work presents BK-style results for welfare (and gains from trade) in two-sided markets, which to the best of our knowledge was not suggested or studied in any prior paper.…”
Section: Additional Related Worksupporting
confidence: 54%
“…The work by Eden et al [2017] found the first such result that beats the optimal revenue for the additive setting, while Feldman et al [2018] improve the bounds on the number of added buyers drastically, but they only recover a (1 − ε)-fraction of the optimal revenue. Very recent work of Beyhaghi and Weinberg [2018] match these bounds in the small market regime and drastically improve the bounds of Eden et al [2017] in the large market regime, even though the [Beyhaghi and Weinberg, 2018] results are for precise coverage of the optimal revenue. While all the above papers presents BK-style results for revenue maximization in one-sided markets, our work presents BK-style results for welfare (and gains from trade) in two-sided markets, which to the best of our knowledge was not suggested or studied in any prior paper.…”
Section: Additional Related Worksupporting
confidence: 54%
“…In other words, these settings are competitive enough for enhanced competition to not yield great gains in the revenue. Thus, the interesting range of parameters is 1 < n ≪ m. See [BW19] for a related result.…”
Section: Our Resultsmentioning
confidence: 91%
“…One key difference between the current work and the foregoing works is that all of them focus on upper bounding the optimal revenue with n bidders by the revenue of an auction that sells the items separately with n ′ bidders, while we also consider VCG auctions with an entry fee. It is known that when restricting attention to auctions that sell the items separately, one cannot get a bound better than n ′ = n • Ω(log m n ) [FFR18,BW19]. Thus, these works cannot hope to get n ′ = O(n) like we do.…”
Section: Related Workmentioning
confidence: 88%
See 1 more Smart Citation
“…Each bidder i is has value v ij for item j, and values the set S of items at j∈S v ij . Such valuations are called additive, and are perhaps the most well-studied valuations in multi-item auction design Nisan, 2012, 2013;Li and Yao, 2013;Babaioff et al, 2014;Daskalakis et al, 2014;Hart and Reny, 2015;Cai et al, 2016;Daskalakis et al, 2017b;Beyhaghi and Weinberg, 2019).…”
Section: Auction Design and Symmetriesmentioning
confidence: 99%